Corporate social responsibility disclosure and corporate governance in Malaysia. (3rd November 2008) - Lim, Ying Zhee; Talha, Mohammad; Mohamed, Junaini; Sallehhuddin, Abdullah
Using 743 Malaysian public listed companies, this study attempts to investigate the impact of corporate governance mechanism on corporate social responsibility (CSR) disclosure level and to examine the difference of CSR disclosure level in government-linked companies and non-government linked companies. Employing multivariate analysis, the study reveals that the presence of larger non-executive directors and a higher involvement of institutional shareholders, which is dummied by government-linked companies cause significant increase in level of CSR disclosure. Besides, even though statistically insignificant, the duality role negatively affects disclosure level. In addition, existence of larger number of independent non-executive directors and employment of big four auditing firms contribute towards increased disclosure of CSR. This study is expected to add to the existing accounting literature by introducing instrument in measuring CSR disclosure and benefits regulators in improving corporate governance initiative in developing economic environment.